Does Tranexamic Acid Prevent Postpartum Haemorrhage? A Systematic Review of Randomized Controlled Trials. Issue 3 (September 2017) - Ker, K.; Shakur, H.; Roberts, I.
Abstract : ( BJOG. 2016;123(11):1745–1752) Postpartum hemorrhage (PPH) is the leading cause of maternal mortality worldwide. When PPH becomes life-threatening it sometimes requires hysterectomy, which deprives women of their ability to bear children in the future. Tranexamic acid (TXA) has been used successfully in trauma patients to control bleeding by inhibiting the breakdown of fibrin clots. Its use for obstetric hemorrhage is currently being evaluated. The authors performed a systematic review of randomized controlled trials to assess the efficacy of TXA to prevent postpartum hemorrhage as well as its effect on other clinically important outcomes.